Impoverishment associated with out-of-pocket health care spending and access to health care in Thailand's 4 regions pre and post Universal Coverage implementation - Thanaporn Bussabawalai (Chulalongkorn University, 2013)
Thesis (M.Sc.)--Chulalongkorn University, 2010